2011
DOI: 10.1002/sia.3421
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the H:C ratio on the sputtering of molecular solids by fullerenes

Abstract: The understanding of the process by which molecular solids are sputtered by keV clusters such as C 60 is of great importance if cluster SIMS is to be routinely used to depth profile a wide range of molecular materials. Computer simulations of the impact of a C 60 cluster on a molecular solid show that an impact crater is produced. At the edges of the crater, a reaction zone is created which contains fragmented and cross-linked molecules. It has been shown previously that this 'reaction zone' can be extensive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“… As was shown in recent simulations of fullerite bombardment with C 60 and Ar clusters, broken and compressed C 60 molecules tend to form a heavily cross‐linked network. Indeed, the nature of C 60 does not favour molecular degradation by scission into smaller volatile entities; rather, the reactive radicals induced by the beam tend to make links with the neighbouring molecules. In SIMS, an increase in such fragment intensity is observed when going from (poly)aromatic structures to more linear structures, which might suggest that the beam tends to affect the polyaromatic structure and form, for instance, more linear bridges between molecules.…”
Section: Resultssupporting
confidence: 56%
“… As was shown in recent simulations of fullerite bombardment with C 60 and Ar clusters, broken and compressed C 60 molecules tend to form a heavily cross‐linked network. Indeed, the nature of C 60 does not favour molecular degradation by scission into smaller volatile entities; rather, the reactive radicals induced by the beam tend to make links with the neighbouring molecules. In SIMS, an increase in such fragment intensity is observed when going from (poly)aromatic structures to more linear structures, which might suggest that the beam tends to affect the polyaromatic structure and form, for instance, more linear bridges between molecules.…”
Section: Resultssupporting
confidence: 56%
“…Using a series of samples including the same octane and octatetraene crystals, in addition to benzene ice and fullerite, Webb et al investigated the effect of the H : C ratio in the sample on the reactions occurring upon C 60 bombardment. 68 Overall, the number of cross-links, defined as new C-C bonds created between adjacent molecules, decreases with increasing H : C ratio. However, fullerite really stands out of the series.…”
Section: Induced Chemistrymentioning
confidence: 99%
“…14 Fullerene-induced cross-linking 68. Number of links between intact molecules as a function of time after the initial impact of a 20 keV C 60 projectile on different molecular targets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Webb et al have recently shown that the number of crosslinks created by 15-20 keV C 60 clusters decreases with increasing H : C ratio in the molecule (going from fullerite to octatetraene to octane). [29] Fullerite appears to be an extreme example of crosslinkable material, with large number of bridges between molecules being formed by each impact. In an ongoing project, we are taking this study one step further by comparing the effect of different projectiles (C 60 , Ar 18 , Ar 60 , Ar 2500 ) on the crosslinking of a fullerite crystal.…”
Section: Sputtering and Energymentioning
confidence: 99%